Seaweed ecology and physiology - Hurd, Catriona L.; Harrison, Paul J. (Paul James), 1941-; Bischof, Kai; Lobban, Christopher S. (Cambridge : Cambridge University Press, 2014)
In coastal seas, from the tropics to the poles, seaweeds supply the energy required to support diverse coastal marine life and provide habitat for invertebrates and fish. Retaining the highly successful approach and structure of the first edition, this is a synthesis of the role of seaweeds in underpinning the functioning of coastal ecosystems worldwide. It has been fully updated to cover the major developments of the past twenty years, including current research on the endosymbiotic origin of algae, molecular biology including'omics', chemical ecology, invasive seaweeds, photobiology and stress physiology. In addition to exploring the processes by which seaweeds, as individuals and communities, interact with their biotic and abiotic environment, the book presents exciting new research on how seaweeds respond to local and global environmental change. It remains an invaluable resource for students and provides an entry into the scientific literature of a wide range of topics.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Marine algae -- Ecophysiology